Body mass index and weight gain after middle adulthood are associated with risk of papillary thyroid cancer: A case–control study. (December 2021) - Hu, Ming-Jun; Zhao, Huan-Huan; Li, Guo-Ao; Zhang, Han-Shuang; He, Jia-Liu; Huang, Fen
Abstract: Background: It is unclear whether weight change after middle adulthood influences the risk of thyroid cancer. The aim of this study was to investigate associations between the risk of papillary thyroid cancer (PTC) and body mass index (BMI) and weight change after middle adulthood (age 35). Methods: A matched case–control study based on three hospitals included 516 pairs of cases newly diagnosed with PTC and controls. Current height and weight after defecation in the morning were measured by trained nurses. During measurement, all subjects were requested to wear lightweight clothing and no shoes. Weight at age 35 was self-reported. BMI and weight change were modeled as continuous and categorical variables. Conditional and unconditional logistic regression models were used to estimate the odds ratio (OR) and 95% confidence interval (95%CI) for the association between BMI and weight change after middle adulthood and PTC. Results: After adjustment for covariates, measured BMI at the time of current diagnosis was positively associated with PTC (OR 1.16, 95%CI 1.10–1.21). According to WHO BMI guidelines for Asia-Pacific populations, the OR (95%CI) for PTC risk in obesity was 2.99 (1.92–4.67) compared to normal weight (p-trend <0.001). Moreover, PTC was positively associated with BMI at age 35; the OR (95%CI) for PTC risk per unit increase in BMI was 1.06 (1.02–1.11). Compared to stable weight (changed <0.5 kg/year), weight gain ≥1.0 kg/year after middle adulthood was positively associated with PTC (OR 2.57, 95%CI 1.39–4.76, p-trend <0.001). Compared to maintaining non-overweight status, the PTC risk was significantly increased in those individuals who gained weight and became overweight after middle adulthood (OR 3.82, 95%CI 2.50–5.85). Conclusion: This study showed that high BMI and obesity were positively associated with increased risk of PTC, and weight gain after middle adulthood also could elevate the PTC risk. Highlights: A matched case-control study describing papillary thyroid cancer in China. Papillary thyroid cancer is associated with high body mass index and obesity. Weight gain since middle adulthood can elevate papillary thyroid cancer risk.